INTERESSES SUBJACENTES E INTERESSES MANIFESTOS NO CONTEXTO DAS USURPAÇÕES ROMANAS (284-395 d.C.) - da Silva, Gilvan Ventura (PHOÎNIX, 2020)
This article aims at analysing the interests of the usurpers and their social groups at the Roman Empire from 284 A.A. up to 395 A.A. In order to carry out our analysis, we've borrowedfrom Political Sciences concepts and theories concerning social conflicts.